Enantioselective comprehensive two‐dimensional gas chromatography of lavender essential oil. Issue 24 (18th November 2016) - Krupčík, Ján; Gorovenko, Roman; Špánik, Ivan; Armstrong, Daniel W.; Sandra, Pat
Abstract : The enantiomeric composition of several chiral markers in lavender essential oil was studied by flow modulated comprehensive two‐dimensional gas chromatography operated in the reverse flow mode and hyphenated to flame ionization and quadrupole mass spectrometric detection. Two capillary column series were used in this study, 2, 3‐di‐ O ‐ethyl‐6‐ O ‐ tert ‐butyldimethylsilyl‐β‐cyclodextrin or 2, 3, 6‐tri‐ O ‐methyl‐β‐cyclodextrin, as the chiral column in the first dimension and α polyethylene glycol column in the second dimension. Combining the chromatographic data obtained on these column series, the enantiomeric and excess ratios for α‐pinene, β‐pinene, camphor, lavandulol, borneol, and terpinen‐4‐ol were determined. This maybe a possible route to assess the authenticity of lavender essential oil.